Military Environmental Security under Radiation and Chemical Threats (Моделювання, керування та інформаційні технології, 2025)
Radiation and chemical hazards pose persistent, often invisible risks to personnel, civilians, infrastructure, and ecosystems in both peacetime and combat operations. This article presents an integrated concept for a military environmental security system that treats sensing, risk assessment, and decision support as a single end to end capability. We synthesize a threat model for radiological and chemical releases, derive quantitative detection and response objectives, and propose a layered architecture spanning tactical sensors, resilient communications, governed data management, streaming analytics, and role specific decision support. The concept targets compression of the detect to act timeline, reduction of uncertainty, and preservation of legal traceability. A consolidated section summarizes design choices, including k out of n resilience, calibration traceability, and anti spoofing safeguards. A notional case outlines performance metrics such as alarm latency, source localization accuracy, and contour forecast error. The approach converts fragmented practices into a repeatable and auditable function that strengthens force protection and reduces ecological harm. The framework supports phased adoption, after action learning, and alignment with national environmental and public health requirements.